ANALISIS PENGARUH LIVE STREAMING SHOPPING, PRICE DISCOUNT, DAN EASE OF PAYMENT TERHADAP IMPULSE BUYING (Studi pada Pengguna Platform Media Sosial TikTok Indonesia) - Nurhaliza, Putri; Kusumawardhani, Amie (Diponegoro Journal of Management, 2023)
ABSTRACT These days, the competition in electronic commerce is increasingly competitive. Business actors will continue to strive to increase product sales, one of which is by stimulating consumers to make unplanned purchases or impulse buying. Strategies that can be applied by business actors to stimulate consumers to do impulse buying are optimizing the use of the live streaming shopping platform e-commerce feature, implementing a price discount promotion strategy and by providing convenience in the payment process. This research was conducted with the aim of examining the effect of Live Streaming Shopping, Price Discounts, and Ease of Payment on Impulse Buying among Indonesian TikTok users. This research is classified as a quantitative research. The sample collection technique used is non-probability sampling with purposive sampling technique. Through distributing questionnaires, a sample of 112 respondents was collected which met the criteria to represent the study population, namely Indonesia TikTok users. The data that has been collected was analyzed using multiple linear analysis methods through SPSS 26 software. The results of data processing from this study show that partially Live Streaming Shopping and Price Discounts have a positive and significant influence on Impulse Buying. Meanwhile, Ease of Payment does not have a significant effect on Impulse Buying. Simultaneously, Live Streaming Shopping, Price Discounts, and Ease of Payment have a positive and significant influence on Impulse Buying